2015
DOI: 10.1103/physrevx.5.011012
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of a Topological Edge Invariant in a Microwave Network

Abstract: We report on the measurement of topological invariants in an electromagnetic topological insulator analog formed by a microwave network, consisting of the winding numbers of scattering matrix eigenvalues. The experiment can be regarded as a variant of a topological pump, with non-zero winding implying the existence of topological edge states. In microwave networks, unlike most other systems exhibiting topological insulator physics, the winding can be directly observed. The effects of loss on the experimental r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
208
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 196 publications
(217 citation statements)
references
References 47 publications
7
208
0
Order By: Relevance
“…This situation stands in sharp contrast to that of static two-dimensional systems, where the existence of chiral edge states is intimately tied to the topological structure of the system's bulk bands, as captured by their Chern numbers [34]. A system exhibiting this anomalous behavior was recently realized using microwave photonic networks [35,36].…”
Section: Introductionmentioning
confidence: 83%
“…This situation stands in sharp contrast to that of static two-dimensional systems, where the existence of chiral edge states is intimately tied to the topological structure of the system's bulk bands, as captured by their Chern numbers [34]. A system exhibiting this anomalous behavior was recently realized using microwave photonic networks [35,36].…”
Section: Introductionmentioning
confidence: 83%
“…5, and is conceptually similar to the experiment previously reported in Ref. 24. The network is designed according to the topological pumping configuration shown in Fig.…”
Section: Methodsmentioning
confidence: 97%
“…Previously, we have shown that such a network, constructed from radio frequency (RF) cables, couplers, and phase shifters, can be used to implement a topological pump. 24 The windings arXiv:1703.01293v1 [physics.class-ph] 3 Mar 2017…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A direct implication of this result is the interface state formed by two PCs with different topological invariants. Recently, interface states in some non-Hermitian systems have been reported [47][48][49]. It is known that for Hermitian systems there is a rigorous mathematical relationship that connects the quantized Zak phase of the bulk bands with the formation of interface states [44].…”
Section: Band Inversion In 1d Pt -Symmetric Pcmentioning
confidence: 99%